IT Project Portfolio Selection in the Presence of Project Interactions - Meier, Christian

On the Activating Power of Gamification – Empirical Evidence from an Online Community - Mutter, Tobias

Does technological change drive inclusive industrialization? A review of major concepts and findings - Gries, Thomas; Grundmann, Rainer; Palnau, Irene; Redlin, Margarete

Simultane bilaterale Verhandlungen - Zur Zusammenstellung eines Sortiments - N, N

Cournot-Nash-Bertrand Wettbewerb im serviceorientierten Internet - N, N

Multilaterale Verhandlungen aus Produzentensicht - N, N

Produktdifferenzierung und Verhandlungsposition im duopolistischen Wettbewerb - N, N

Aggregating Online Reputation Feedback - N, N

Verhandlungserfolg durch Reduktion von Verhandlungsasymmetrien - eine Analyse mit dem Adjusted-Winner-Verfahren - N, N

Different Sources of the Variance of Online Consumer Ratings and their Impact on Price and Demand - Herrmann, Philipp; Kundisch, Dennis; Zimmermann, Steffen; Nault, Barry

Real-time Business Process Intelligence. Comparison of different architectural approaches using the example of the order-to-cash process. - Korotina, Anastasiia; Müller, Oliver; Debortoli, Stefan (International Conference on Wirtschaftsinformatik)
Business operations are becoming more and more integrated with the real-time intelligence. Core business activities are being carried out through OLTP systems that provide limited monitoring capabilities of the running process instances. The article shows how to turn the gap between the classic transactional system and the process-centric approach into an organization that provides more accurate and faster decisions on the strategic and operational management levels. This study aims at determination of what kind of information can be retrieved during the process execution and it tries to identify the need for the real-time process intelligence on the example of the order-to-cash process. Furthermore, we compare two architectural approaches of the real-time process intelligence monitoring system. The proposed frameworks retrieve process data from the ERP system in order to record crucial performance indicators on a real-time basis with the use of the in-memory technology.

Determinants of loan securitization in European banking - Farruggio, Christian; Uhde, André (Journal of Banking and Finance)
Analyzing 75 securitizing and non-securitizing stock-listed banks in the EU-13 plus Switzerland over the period from 1997 to 2010, this paper provides empirical evidence that loan securitization in Europe is a composite decision based on bank-specific as well as market- and country-specific determinants. In addition, we find that these determinants remarkably change when separately investigating securitization transactions during the pre-crisis and crisis period. Moreover, results from several subsample regressions reveal that determinants of loan securitizations in Europe depend on the transaction type, the underlying asset portfolio and the regulatory and institutional environment under which banks operate.
Keywords: Securitization; Determinants; European banking

Does mandatory IFRS adoption facilitate debt financing? - Florou, Annita; Kosi, Urska (Review of Accounting Studies)
We examine whether the mandated introduction of International Financial Reporting Standards (IFRS) is associated with the propensity to access the public rather than private debt market and the cost of debt. We use a global sample of public bonds and private loans and find that mandatory IFRS adopters are more likely, post-IFRS, to issue bonds than to borrow privately. We also find that mandatory IFRS adopters pay lower bond yield spreads, but not lower loan spreads, after the mandate. These findings are consistent with debt providers responding positively to financial reporting of higher quality and comparability, but only when there is a greater reliance on publicly available financial statements than private communication. Lastly, we document that the observed debt market benefits are concentrated in countries with larger differences between domestic GAAP and IFRS and are present even for EU countries that did not experience concurrent financial reporting enforcement or other institutional reforms. Overall, our study documents positive economic consequences around the mandated IFRS adoption for corporate debt financing and, in particular, for bond financing.
Keywords: Accounting regulation; IFRS; Accounting quality; Public and private debt markets; Cost of debt

Uncertainty in Weighting Formulary Apportionment Factors - Ortmann, Regina (Die Betriebswirtschaft)

Uncertainty in Weighting Formulary Apportionment Factors. How Does Weighting Uncertainty Impact After-Tax Income of Multinational Groups? - Ortmann, Regina (Die Betriebswirtschaft)

Investitionsneutrale Besteuerung des ökonomischen Gewinns: ein Abriss jüngerer Forschungsbeiträge - Diller, Markus; Grottke, Markus; Lorenz, Johannes (Wirtschaftswissenschaftliches Studium (WiSt))

Tax Aggressiveness of Taxpayers with Heterogenous Income and Uncertainty about Taxable Income - Diller, Markus; Lorenz, Johannes (FinanzArchiv / Public Finance Analysis)

Short-and medium-term effects of informal care provision on female caregivers’ health - Schmitz, Hendrik; Westphal, Matthias (Journal of Health Economics)

Threatening customers not to return – An effective strategy for online retailers? - Feider, L.; Garnefeld, I.; Böhm, Eva (44th EMAC Annual Conference, Leuven)

Stock market reactions to customer service outsourcing in manufacturing firms - Eggert, A.; Böhm, Eva; Cramer, C. (2015 AMA Winter Academic Conference, San Antonio, TX)

Recognizing value creation opportunities in business markets - Böhm, Eva; Eggert, A.; Terho, H.; Ulaga, W.; Haas, A. (2015 AMA Winter Academic Conference, San Antonio, TX)

Stock market reactions to business service outsourcing in manufacturing firms - Eggert, A.; Böhm, Eva; Cramer, C. (44th EMAC Annual Conference, Leuven)

Organizations, Climate Change, and Transparency - Hahn, Rüdiger; Reimsbach, Daniel; Schiemann, Frank (Organization & Environment)
The debate surrounding climate change often centers on companies’ contributions to global warming, which has led to an increase in the importance of carbon disclosure. We evaluate the current state of related research and identify its trends, coherences, and caveats via a systematic literature review. Sociopolitical theories of disclosure, economic theories of disclosure, and institutional theory serve as the main theoretical anchors for our exploration. The existing research emphasizes the determinants and, to a lesser extent, effects of carbon disclosure, as well as the associated regulatory issues such as voluntary versus mandatory disclosure. Additionally, we discuss related topics, such as assurance and risks. We find that a large portion of scholarly work provides no link to theory, despite the fact that such links can be identified, for example, from the financial disclosure literature. Finally, we report on the established knowledge and examine the need for additional research.
Keywords: Organizational Behavior and Human Resource Management; General Environmental Science

Cross-cutting organizational and demographic divides and the performance of research and development teams: two wrongs can make a right - Iseke, Anja; Kocks, Birgit; Schneider, Martin; Schulze-Bentrop, Conrad (R&D Management)

Testing vs. building accounting theory with experimental research: insights from management research - Reimsbach, Daniel; Hauschild, Bastian (International Journal of Behavioural Accounting and Finance)
Keywords: Geology; Ocean Engineering; Water Science and Technology

Open Educational Resources in der aktuellen Bildungslandschaft: Motivation zur Teilung und Nutzung. - Beutner, Marc; Schneider, Jennifer Nicole (Kölner Zeitschrift für Wirtschaft und Pädagogik)

The Contingent Role of Centrality in IT Network Governance: An Empirical Examination - Trang, S.; Zander, S.; Kolbe, L. M. (Pacific Asian Journal of the Association for Information Systems)

Analyse der Anwendbarkeit von Six Sigma als Instrument der Investitionsplanung - Heitmann, Ingmar (Ausgewählte Probleme des Logistikmanagements)

Konzeption eines Logistikcontrollingansatzes zur Abwicklung zeitkritischer Transportvorgänge - Puls, Christoph (Ausgewählte Probleme des Logistikmanagements)

Entwicklung eines qualitativen Verfahrens zur Bewertung logistischer Investitionen - Koch, Christian (Ausgewählte Probleme des Logistikmanagements)

Klassenspezifische und zeitraumbezogene Logistikmengenprognose - Ortgiese, Malte (Ausgewählte Probleme des Logistikmanagements)

Verrechnungspreise in Speditionskooperationen - Opitz, Oliver (Ausgewählte Probleme des Logistikmanagements)

Verrechnungspreise in Speditionskooperationen - Faupel, Christian (Ausgewählte Probleme des Logistikmanagements)

Managing the Bright and Dark Sides of Status Endowment in Hierarchical Loyalty Programs - Eggert, A.; Steinhoff, Lena; Garnefeld, I. (Journal of Service Research)

You Might Want to Engage Your Customers, But Choose Them Wisely: The Mixed Effects of Company-Initiated Customer Engagement on Customer Loyalty - Eggert, A.; Steinhoff, Lena; Witte, C. (2015 AMA Summer Marketing Educators’ Conference Proceedings, Chicago)

Open Educational Resources in der aktuellen Bildungslandschaft: Motivation zur Teilung und Nutzung - Beutner, Marc; Schneider, Jennifer Nicole (Kölner Zeitschrift für Wirtschaft und Pädagogik)

EU-StORe- Creating European Standards for Open Education and Open Learning Resources - Schneider, Jennifer Nicole

Research on didactical material and open learning resources - Schneider, Jennifer Nicole

Training Courses and Implementation - Schneider, Jennifer Nicole

The EU-StORe-Survey - Schneider, Jennifer Nicole

Evaluation of the first Prototype version of AGnovel - Schneider, Jennifer Nicole

Evaluation - Schneider, Jennifer Nicole

On the assessment of attitudes towards studying—development and validation of a questionnaire - Brahm, Taiga; Jenert, Tobias (Learning and individual differences : journal of psychology and education)
This research aims to develop and validate an instrument for the assessment of attitudes towards two particular objects: the Higher Education Institution (HEI) and the process of studying. Investigating attitudes towards studying at a HEI in a comprehensive way addresses an important research gap. It connects students' perception of the institution with teaching and learning. To validate the Assessment of Students' Attitudes towards Studying (ASAtS) Questionnaire, data was gathered at three different universities in Switzerland (820 students), Sweden (167) and Germany (133). Overall, the results show the internal consistency of the ASAtS. Its nomological validity is also supported by correlations with other constructs, such as intrinsic motivation and study performance. The ASAtS contributes to the theory on students learning by broadening the scope of research beyond learning in a narrow sense. From a practical point of view, it provides a tool for HE management to monitor students' perception of their HEI.
Keywords: Attitude; Student learning; Higher Education Institution; university; student experience

Vermögensteuer und ihre Implikationen für den Wirtschaftsstandort Deutschland - eine betriebswirtschaftliche Analyse - Hoppe, Thomas; Maiterth, Ralf; Sureth-Sloane, Caren
Die (Wieder-)Einführung einer Vermögensteuer ist in den vergangenen Jahren erneut in den Fokus der politischen Diskussion gerückt. Der vorliegende Beitrag vermittelt einen Eindruck von den Belastungswirkungen, die aus der Umsetzung von aktuell vorliegenden Besteuerungskonzepten resultieren würden. Auf der Basis von realen Jahresabschlussdaten wird eine mehrperiodige Veranlagungssimulation durchgeführt, die insbesondere ermöglicht, den zu erwartenden Eigenkapitalverzehr sowie den Anstieg der Steuerbelastung für die betrachtete Unternehmensgruppe zu quantifizieren. Von besonderem Interesse sind hierbei Unternehmen deren laufende Erträge nicht ausreichen, um die Belastungen durch die Vermögensteuer zu tragen und damit einem Substanzverzehr ausgesetzt sind. Es zeigt sich, dass etwa die Hälfte der Unternehmen im Untersuchungszeitraum von sechs Jahren in mindestens einem Jahr einen Substanzverzehr erfährt. Der Vermögensteuer kommt somit keinesfalls der vielfach postulierte Charakter einer eher mäßig belastenden und im Wesentlichen substanzverschonenden Steuer zu. Zusatzbelastungen von knapp 100 bis zu 300% der Ertragsteuerlast sind keine Seltenheit und veranschaulichen das Gefährdungspotenzial dieser Steuer für den Wirtschaftsstandort Deutschland.
Keywords: Steuerbelastung; Substanzbesteuerung; ungleiche Vermögensverteilung; Veranlagungssimulation; Vermögensteuer

Die Rückforderung unzulässiger Bearbeitungsentgelte im Spannungsfeld von Rechtsfrieden und Verbraucherschutz - Bartlitz, David (Zeitschrift für Bank- und Kapitalmarktrecht (BKR))

Wirksamkeit von Bearbeitungsentgelten in Darlehensverträgen mit Unternehmern. Anmerkung zu LG Kleve, Urt. v. 18.08.2015 - 4 O 13/15 - Bartlitz, David (Entscheidungen zum Wirtschaftsrecht (EWiR))

Competitive outcomes and the inner core of NTU market games - Brangewitz, Sonja; Gamp, Jan-Philip (Economic Theory)

A Technical Concept for Plant Engineering by Simulation-Based and Logistic-Integrated Project Management - Gutfeld, Thomas; Jessen, Ulrich; Wenzel, Sigrid; Laroque, Christoph; Weber, Jens (Proceedings of the 2014 Winter Simulation Conference)

A Data Mining Approach to Support a Data-Driven Scheduling System for Air Cargo Terminals - Boxnick, Simon; Lauck, Sebastian; Weber, Jens (Proceedings of the IEEE Asia-Pacific World Congress on Computer Science and Engineering 2014 (APWC on CSE 2014))

Experiments using Meta-Heuristics to Shape Experimental Design for a Simulation-Based Optimization System: Intelligent Configuration and Setup of Virtual Tooling - Weber, Jens; Boxnick, Simon; Dangelmaier, Wilhelm (Proceedings of the IEEE Asia-Pacific World Congress on Computer Science and Engineering 2014 (APWC on CSE 2014))

Applying GPU Programming to Obtain Average AS/RS Performance in Optimal Zoned Aisles - Lauck, Sebastian; Boxnick, Simon; Kopecki, Lukas (Proceedings of the IEEE Asia-Pacific World Congress on Computer Science and Engineering 2014 (APWC on CSE 2014))

Analyzing Supply Chain nodes in Heterogeneous Environments based on Transaction Data with Respect to Independent item Behavior - Lauck, Sebastian; Boxnick, Simon; Kopecki, Lukas (Proceedings of the 2nd International Conference on Advances in Computing, Electronics and Communication (ACEC-2014))

System Thinking: Crafting Scenarios for Prescriptive Analytics - Weber, Jens; Minhee, Cho; Lee, Mikyoung; Song, Sa-kwang; Geierhos, Michaela; Jung, Hanmin (Proceedings of the First International Workshop on Patent Mining and Its Applications (IPAMIN) 2014)

SentiBA: Lexicon-based Sentiment Analysis on German Product Reviews - Dollmann, Markus; Geierhos, Michaela (Konvens 2014 Workshop Proceedings)

Linked Open Data System for Scientific Data Sets - Baeumer, Frederik Simon; Gim, Jangwon; Jeong, Do-Heon; Geierhos, Michaela; Jung, Hanmin (Proceedings of the First International Workshop on Patent Mining and Its Applications (IPAMIN) 2014)

Are Requirements for Graduates of Master and PhD Programs in Business and Information Systems Engineering Changing? - Eymann, T.; Kundisch, Dennis

Should I Stay or Should I Go - Eymann, T.; Kundisch, Dennis; Recker, J.

Trade and fertility in the developing world: the impact of trade and trade structure - Gries, Thomas; Grundmann, Rainer (Journal of Population Economics)

Ändern sich die beruflichen Anforderungen an Masterabsolventen und Doktoranden der Wirtschaftsinformatik? - Eymann, T.; Kundisch, Dennis

Should I Stay or Should I Go - Herausforderungen und Chancen eines Wechsels zwischen Hochschulsystemen - Eymann, T.; Kundisch, Dennis; Recker, J.

Vorwort der Tagungsleitung - Suhl, Leena; Kundisch, Dennis

Household Savings and Productive Capital Formation in Rural Vietnam: Insurance vs. Social Network - Gries, Thomas; Dung, Ha Van (Modern Economy)

The same but not the same - Challenges in comparing patient opinions - Geierhos, Michaela; Schulze, Sabine

What is research ethics observing? An interdisciplinary {\ "a} re discussion between computational linguistics and qualitative-constructivist social research} - Geierhos, Michaela; Siri, Jasmin (Proceedings Research Ethics in Qualitative and Quantitative Social Research)

Ans {\ "a} sets for ü r an online optimization of the lot sizes in the Series production - Dangelmaier, Wilhelm

Modeling of the PLC Behavior in Intralogistics with Non-Autonomous Hybrid Petri-Nets - Kopecki, Lukas; Lauck, Sebastian

Information Systems for Composite Materials: Requirements and Challenges - Dangelmaier, Wilhelm; Sommer-Dittrich, Thomas; Streichhan, Jenny; Monhof, Markus (Applied Mechanics and Materials)

Comparative study on disambiguating acronyms in the scientific papers using the open knowledge base - Jeong, Do-Heon; Gim, Jangwon; Jung, Hanmin; Geierhos, Michaela; Baeumer, Frederik Simon (Proceedings of the 9th Asia Pacific International Conference on Information Science and Technology)

An Evolutionary Approach on Multi-objective Scheduling for Evolving Manufacturing Systems - Klöpper, Benjamin; Pater, Jan-Patrick; Dangelmaier, Wilhelm (Proceedings of the 47th Annual Hawaii International Conference on System Sciences)
New paradigms for designing manufacturing systems, such as adaptive and service-oriented manufacturing systems or self-optimizing resources, introduce new degrees of freedom into manufacturing control. These paradigms lead to the research question how human decision makers can be enabled to exploit the high adaptability of the new manufacturing systems in accordance to the current requirements arising from quickly changing market requirements and demand for sustainable manufacturing. This contribution extends a scheduling model for self-optimizing and service-oriented manufacturing systems through the consideration of alternative resources and introduces a multi-objective scheduling concept based on evolutionary algorithms in combination with a new optimized type of crossover operator.

Acceleration of Materialflow Simulations Using Model Coarsening by Token Sampling and Online Error Estimation and Accumulation Controlling - Renken, Hendrik

Towards a Local Grammar-based Persondata Generator for Wikipedia Biographies - Geierhos, Michaela (Penser le Lexique-Grammaire)

Development of the RailCab Vehicle - Flaßkamp, Kathrin; Grösbrink, Stefan; Hartmann, Philip; Heinzemann, Christian; Kleinjohann, Bernd; Kleinjohann, Lisa; Krüger, Martin; Ober-Blöbaum, Sina; Priesterjahn, Claudia; Rasche, Christoph; Schäfer, Wilhelm; Steenken, Dominik; et al. (Dependability of Self-Optimizing Mechatronic Systems)

Outsourcing von Lagerdienstleistungen als operatives Entscheidungsproblem - Betz, Stefan (Logistikorientiertes Produktionsmanagement)

Beating Irrationality: Does Delegating to IT Alleviate the Sunk Cost Effect? - Herrmann, Philipp; Kundisch, Dennis; Rahman, Mohammad (Management Science)

Using Income Accounting as the Theoretical Basis for Measuring IT Productivity - Kundisch, Dennis; Mittal, Neeraj; Nault, Barrie (Information Systems Research)

Don't take away my Status! - Evidence from the Restructuring of a Virtual Reward System - Mutter, Tobias; Kundisch, Dennis (Computer Networks)

Business Models - An Information Systems Research Agenda - Veit, Daniel; Clemons, Eric; Benlian, Alexander; Buxmann, Peter; Hess, Thomas; Kundisch, Dennis; Leimeister, Jan-Marco; Loos, Peter; Spann, Martin (Business & Information Systems Engineering)

Geschäftsmodelle - Eine Forschungsagenda für die Wirtschaftsinformatik - Veit, D.; Clemons, E.; Buxmann, A.; Hess, T.; Kundisch, Dennis; Leimeister, J.-M.; Loos, P.; Spann, M. (Wirtschaftsinformatik)

Analyzing Cost and Risk Interaction Effects in IT Project Portfolios - Heinrich, B.; Kundisch, Dennis; Zimmermann, Steffen (BIT - Banking and Information Technology)

Low Carbon Economics - Theory and application - Gries, Thomas (Low Carbon Economics)

Zur Ausbreitung und Behinderung von Epidemien - Eine Netzwerkanalyse - Drigalsky, Liesa

Finanzierung - Grundlagen, Institutionen, Instrumente und Kapitalmarkttheorie - Gräfer, Horst; Schiller, Bettina; Rösner, Sabrina
Dieses Lehr- und Arbeitsbuch präsentiert Ihnen die wichtigsten Grundlagen der Unternehmensfinanzierung auf dem neuesten fachlichen Stand. Der perfekte Einstieg in ein zentrales finanzwirtschaftliches Fach- und Praxisgebiet – mit vielen Beispielen und Übungen.
Keywords: Management; Wirtschaft

IT-basierte Dienstleistungen für die Elektromobilität --- Konzeptioneller Rahmen und Literaturanalyse - Klör, Benjamin; Bräuer, Sebastian; Beverungen, Daniel; Matzner, Martin (Proceedings of the Multikonferenz Wirtschaftsinformatik 2014 (MKWI 2014))

Towards a Flexible and Privacy-Preserving Reputation System for Markets of Composed Services - Brangewitz, Sonja; Jungmann, Alexander; Petrlic, Ronald; Platenius, Marie Christin (Proceedings of the 6th International Conferences on Advanced Service Computing (SERVICE COMPUTATION))
One future goal of service-oriented computing is to realize global markets of composed services. On such markets, service providers offer services that can be flexibly combined with each other. However, most often, market participants are not able to individually estimate the quality of traded services in advance. As a consequence, even potentially profitable transactions between customers and providers might not take place. In the worst case, this can induce a market failure. To overcome this problem, we propose the incorporation of reputation information as an indicator for expected service quality. We address On-The-Fly Computing as a representative environment of markets of composed services. In this environment, customers provide feedback on transactions. We present a conceptual design of a reputation system which collects and processes user feedback, and provides it to participants in the market. Our contribution includes the identification of requirements for such a reputation system from a technical and an economic perspective. Based on these requirements, we propose a flexible solution that facilitates the incorporation of reputation information into markets of composed services while simultaneously preserving privacy of customers who provide feedback. The requirements we formulate in this paper have just been partially met in literature. An integrated approach, however, has not been addressed yet.

On the Ontological Expressiveness of Conceptual Modeling Grammars for Service Productivity Management - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Peter Rauer, Hans; Sigge, Daniel (Information Systems and e-Business Management)

Exploring the Interplay of the Design and Emergence of Business Processes as Organizational Routines - Beverungen, Daniel (Business and Information Systems Engineering)

Über das Zusammenwirken der Gestaltung und Emergenz von Geschäftsprozessen als Organisationsroutinen - Beverungen, Daniel (WIRTSCHAFTSINFORMATIK)

The Interaction of Signals: A Fuzzy set Analysis of the Video Game Industry - Kaimann, Daniel; Cox, Joe
Customers continuously evaluate the credibility and reliability of a range of signals both separately and jointly. However, existing econometric studies pay insufficient attention to the interactions and complex combinations of these signals, and are typically limited as a result of difficulties controlling for multicollinearity and endogeneity in their data. We develop a novel theoretical approach to address these issues and study different signaling effects (i.e., word-of-mouth, brand reputation, and distribution strategy) on customer perceptions. Using data on the US video games market, we apply a fuzzy set qualitative comparative analysis (fsQCA) to account for cause-effect relationships. The results of our study address a number of key issues in the economics and management literature. First, our results support the contention that reviews from professional critics act as a signal of product quality and therefore positively influence unit sales, as do the discriminatory effects of prices and restricted age ratings. Second, we find evidence to support the use of brand extension strategies as marketing tools that create spillover effects and support the launch of new products.

The Economics of Individual Behavior in Competitive Environments: Empirical Evidence from Real-Life Tournaments - Scheel, Friedrich

Customer collectives in healthcare: The transformative potential of service to overcome consumer vulnerability - Rötzmeier-Keuper, Julia; Wünderlich, Nancy (Proceedings of the 39th Annual Macromarketing Conference)

Interdependent Relationships Between and among Service Providers and Customer Collectives. - Rötzmeier-Keuper, Julia; Wünderlich, Nancy (Proceedings of the AMA SERVSIG International Service Research Conference)

Strategic and Cooperative Games in Network Economics - Röhl, Nils

Signalisieren und Screening in Arbeitsmärkten - die Experimente von Brandts & Holt und Kübler et. al - Kaiser, Sarah

The challenge of assessing the market value of private companies using a standardised combination method for tax purposes--Lessons to be learnt from past experience - Müller, Jens (European Accounting Review)
When taxes on capital or wealth are levied, in most countries companies have to be assessed in terms of their market value (MV). Estimating the MV of private companies for tax purposes is a challenging task for tax authorities as MVs are not available. In this study, I empirically analyse to what extent an accounting-based tax valuation method for private companies, a simplified residual income model, succeeds in matching the MV. I refer to the mandatory Standardised Combination Model that is a special case of methods commonly used in several countries. In the absence of market prices for private companies, I use a sample of small German public companies as a proxy. I validate this approach using a sensitivity analysis that involves matching the sample of public companies with that of private companies. The results imply that the mandatory Standardised Combination Model leads to a severe unequal treatment not only between public and private companies but also among private companies across and within industries. Furthermore, I simulate the effects of variation in the key parameters and highlight their impact on the approximation quality of the Standardised Combination Method. The findings are relevant to tax reform discussions as well as to tax policy-makers and practitioners in many countries.
Keywords: Challenge of Assessing; Tax Purposes

Provider Competition in Infrastructure-as-a-Service - Künsemöller, Jörn; Brangewitz, Sonja; Karl, Holger; Haake, Claus-Jochen (Proceedings of the 2014 IEEE International Conference on Services Computing (SCC))
This paper explores how cloud provider competition inﬂuences instance pricing in an IaaS (Infrastructure-as-a-Service) market. When reserved instance pricing includes an on-demand price component in addition to a reservation fee (two-part tariffs), different providers might offer different price combinations, where the client’s choice depends on its load proﬁle. We investigate a duopoly of providers and analyze stable market prices in two-part tariffs. Further, we study offers that allow a speciﬁed amount of included usage (three-part tariffs). Neither two-part nor three-part tariffs produce an equilibrium market outcome other than a service pricing that equals production cost, i.e., complex price structures do not signiﬁcantly affect the results from ordinary Bertrand competition.

Behavioral Mechanisms Prompted by Badges: The Goal-Gradient Hypothesis - Mutter, Tobias; Kundisch, Dennis (Proceedings of the International Conference on Information Systems (ICIS))

The Hunt for Quality in a Market: Exploring the Relationship between Local Market Structure and Digitized Customer Experience - Herrmann, Philipp

Too Much of a Good Thing? Welfare Consequences of Market Transparency - Gu, Yiquan; Hehenkamp, Burkhard (Journal of Institutional and Theoretical Economics JITE)
This paper studies welfare consequences of consumer-side market transparency with endogenous entry of firms. Different from most studies, we consider the unique symmetric entry equilibrium, which is in mixed strategies. We identify two effects of market transparency on welfare: a competition effect and a novel market-structure effect. We show, surprisingly, that for almost all demand functions the negative market-structure effect eventually dominates the positive competition effect as the market becomes increasingly transparent. Consumer-side market transparency can therefore be socially excessive even without collusion. The only exception among commonly used demand functions is the set of constant demand functions.

The Hunt for Quality in a Market: Exploring the Relationship between Local Market Structure and Digitized Customer Experience - Herrmann, Philipp; Rahman, Mohammad (Workshop on Information Systems & Economics (WISE))

Modeling Languages for Business Models as Tools for Innovation: Towards a Theoretical Foundation - John, Thomas (Proceedings of the Americas' Conference on Information Systems (AMCIS))